A brand preference and repurchase intention model: the role of consumer experience. Issue 13 (1st September 2016) - Ebrahim, Reham; Ghoneim, Ahmad; Irani, Zahir; Fan, Ying
ABSTRACT: Consumer brand preference is an essential step towards understanding consumer choice behaviour, and has therefore always received great attention from marketers. However, the study of brand preference has been limited to traditional marketing focusing on functional attributes to maximise utility. But now the shift to experiential marketing broadens the role of the brand from a bundle of attributes to experiences. Technological advancements have helped to increase the similarities between brand attributes and product commoditisation. Consequently, consumers cannot shape their preferences among brands using rational attributes only. They seek out brands that create experiences; that intrigue them in a sensorial, emotional and creative way. This study seeks to develop a model that provides an understanding of how brand knowledge and brand experience determine brand preference and to investigate its impact on brand repurchase intention. Accordingly, exploratory focus group discussions are employed followed by a survey of mobile phone users in Egypt. The findings provide insights into the relative importance of consumer perceptions on different brand knowledge factors in shaping brand preferences. It also demonstrates the significance of consumers' experiential responses towards brands in developing their brand preferences that in turn influence brand repurchase intention. The model therefore offers managers a new perspective for building strong brands able to gain consumer preferences.